Workplace Violence Toward Mental Healthcare Workers Employed in Psychiatric Wards - Gabriele d'Ettorre; Vincenza Pellicani (Elsevier, 2017)
Background: Workplace violence (WPV) against healthcare workers (HCWs) employed in psychiatric inpatient wards is a serious occupational issue that involves both staff and patients; the consequences of WPV may include increased service costs and lower standards of care. The purpose of this review was to evaluate which topics have been focused on in the literature and which are new in approaching the concern of patient violence against HCWs employed in psychiatric inpatient wards, in the past 20 years. Methods: We searched for publications in PubMed and Web of Science using selected keywords. Each article was reviewed and categorized into one or more of the following four categories based on itsÂ subject matter: risk assessment, risk management, occurrence rates, and physical/nonphysical consequences. Results: Our search resulted in a total of 64 publications that matched our inclusion criteria. The topics discussed, in order of frequency (from highest to lowest), were as follows: ârisk assessment,â ârisk management,â âoccurrence rates,â and âphysical/nonphysical consequences.â Schizophrenia, young age, alcohol use, drug misuse, a history of violence, and hostile-dominant interpersonal styles were found to be the predictors of patientsâ violence. Conclusion: Risk assessment of violence by patients appeared the way to effectively minimize the occurrence of WPV and, consequently, to better protect mental HCWs. We found paucity of data regarding psychologic sequelae of WPV. According to these findings, we suggest the need to better investigate the psychologic consequences of WPV, with the aim of checking the effective interventions to assist HCW victims of violence and to prevent psychologic illness. Keywords: assaults, psychiatric inpatients, risk assessment, risk management, violence